渗碳淬火齿轮变形控制的研究 - 陈建光 (Jixie chuandong)
The proportion of hardened gear in gear processing increase steeply,and the carburizing and quenching is the main process.But the deformation problem after carburizing quenching is seriously affecting the quality of gear processing after heat treatment.Through the reason analysis and experiment,summarizing the experience and take some effective countermeasures,the quality of carburized gear is increased after heat treatment.